Dry Flowers – A Boon to Floriculture Industry - Sharavani, Ch Sai Ratna; sree, G Divya (Journal of Postharvest Technology, 2018)
Dry flowers in floriculture have been gaining impetus with the rapidly growing floriculture industry in India. Value addition in form of floral or plant part drying increases the economic value and consumer appeal of floricultural commodities. Dried flowers are exported as assortments of value added items. In this review the scattered information and data on Indian market of Dried flowers, plants and plant materials suitable for drying and different drying methods of flowers and other ornamental plant parts, packing and transportation are being compiled which would be useful for further studies. This can eventually be helpful in drawing the attention of the researchers and scientists to work on it.